Game-Based Language Learning: Implementing Arabic Speaking Proficiency through Truth or Dare with Spin Wheel - Hasibuan, Renni; Jundi, Muhammad; Ali, Ibadurrahman; Febriani, Suci Ramadhanti; Bedra, Kddour Guettaoi (UIN Mahmud Yunus Batusangkar, Indonesia, 2024)
Game-based learning, incorporating both digital and traditional methods, has been extensively researched over the past decade. The current research aimed to conduct an in-depth investigation into implementation of the Truth or Dare with Spin the Wheel game in Arabic speaking learning. This research employs a qualitative approach, integrating observation and interviews, conducted within a learning environment consisting of 34 students. The results revealed that the implementation of Truth or Dare with Spin the Wheel in Arabic speaking learning involved three stages. First, preparation included setting up the Spin the Wheel application and preparing Truth or Dare questions. Next, the opening stage introduced the learning flow using the game. Then, the core stage had students actively participating by responding to questions or challenges in Arabic, followed by evaluation of their responses in the final stage. The game was considered successful in increasing students' active engagement in speaking Arabic, this is supported by observational data showing a 40% increase in student participation during game sessions compared to regular class activities, with each student taking an average of 3 speaking turns per session with the game versus just 1 turn per session in traditional methods, alongside a 50% rise in peer interactions, a 35% increase in teacher-student interactions, and a notable boost in confidence levels, as evidenced by more students volunteering to participate without hesitation. Future research is recommended to explore the long-term impact of using the Truth or Dare with Spin the Wheel game in Arabic speaking learning.